Los Elementos Floristicos de la Formacion Siripaca (Grupo Ambo, Bolivia) y su Contexto Bioestratigrafico - IANUZZI, ROBERTO; DIAZ-MARTINEZ, ENRIQUE; SUAREZ-SORUCO, RAMIRO (Pesquisas em Geociências, 1999)
The fossil flora of the Siripaca Formation (Ambo Group, Copacabana Peninsula, Bolivia) was originally characterized by two endemic taxa: Nothorhacopteris kellaybelenensis and Triphyllopteris boliviana. Other taxa of this flora were recently collected and are described here: Paulophyton sommeri, Diplothmema bodenbenderi and Sphenopteridium intermedium. The biostratigraphic value of all the fossil plants described for the Siripaca Formation is here analysed considering these new elements and their presence in other Gondwana floras. We propose a late Visean to earliest Serpukhovian (latest Early Carboniferous) age for the flora in the Siripaca Formation. The biochrons of these elements within South America are also proposed.